Tacit knowledge as a gift: sociology of the managerial culture in old China - M. Yu. Zakharov; O. V. Kryshtanovskaya; A. A. Komarova (Вестник университета)
The interpretation of the concept of «knowledge» in spiritual culture of old China has been considered. The main ways of its acquirement and use in society has been identified. The nature of tacit knowledge and one of the available ways of its transfer as a gift have been analyzed. For this purpose, specifics of a Chinese gift has been studied, an attempt of understanding the act of gifting in the cognitive sphere has been made. A conclusion about the prospects of this approach for studying the problems of sociology of the Chinese managerial culture as an important component element of the mechanism of governing the Celestial Kingdom has been made.